Relationship between anaemia, coagulation parameters during pregnancy and postpartum haemorrhage at childbirth: a prospective cohort study - Nair, M; Chhabra, S; Choudhury, SS; Deka, D; Deka, G; Kakoty, SD; Kumar, P; Mahanta, P; Medhi, R; Rani, A; Rao, S; Roy, I; et al. (BMJ Publishing Group, 2021)
Objectives To investigate the association between coagulation parameters and severity of anaemia (moderate anaemia: haemoglobin (Hb) 7–9.9 g/dL and severe anaemia: Hb <7 g/dL) during pregnancy and relate these to postpartum haemorrhage (PPH) at childbirth.